KNOWLEDGE OF TRADITIONAL MEDICINE PROCESSING FOR TREATMENT OF HIV/AIDS FOR VOCATIONAL STUDENTS - Indri Hasan; Frezy Paputungan; Imam Mashudi (Jurnal Ilmu Pendidikan dan Budaya, 2023)
Issues regarding HIV/AIDS From the past until now, the problem of HIV/AIDS is not only a problem that occurs at the local level, but has become a regional and global problem. This problem has caused many victims, both children and adults, and has even shaken family life. HIV not only has medical impacts but also psychosocial-spiritual impacts. This condition is very worrying if it is not treated quickly and appropriately. The Indonesian nation will lose a productive young generation. Therefore, to suppress the spread of this virus, it requires the involvement and support of various parties, especially families, in treatment and care so that those infected with HIV have a longer life. An important finding in the world of medicine to suppress the proliferation of the HIV virus is antiretroviral (ARV) drugs which must be consumed regularly. ARVs cannot kill the HIV virus in the body, but they can suppress the reproduction of the virus. The most rapid cases of transmission and development of HIV/AIDS are concentrated in third world countries, where people are still struggling with the problems of educational, economic backwardness, and especially access to inadequate or affordable health services. Lack of education and poor economic conditions mean that people do not carry out regular health checks, resulting in the emergence of various diseases, including HIV/AIDS. Based on research, there were 34.0 billion (31.4-35.9 billion) people living with HIV at the end of 2011. It is estimated that 0.8% of people in the world aged 15-49 years were living with HIV with the highest incidence in Sub-Saharan Africa. Based on statistics on HIV/AIDS cases in Indonesia in 2013 by the Directorate General of PP & PL, Ministry of Health of the Republic of Indonesia, the number of HIV cases reached 118,792, ranking first in the province of Papua. The skin disorders that often occur in HIV/AIDS patients are opportunistic infections. Opportunistic infections become more common in untreated advanced stages of HIV disease, including various causes including bacteria, viruses and fungi.